Changes in Analytes Related to Immunity in the Saliva of Pigs After Vaccination Against Lawsonia intracellularis - Andrea Martínez-Martínez; Manuel Toledo; Emilio Ruiz; Simón García; Anabel Fernández; José Joaquín Cerón; Rut Menjon; María Teresa Tejedor; Elena Goyena; Alberto Muñoz-Prieto (Immuno)
Lawsonia intracellularis is a Gram-negative, intracellular bacterium that can infect several animal species. In pigs, the bacteria cause porcine proliferative enteropathy, or ileitis. The wide spread of the pathogen produces a large impact on pig production worldwide. Saliva is a source of biomarkers that can help to monitor changes in the immune system after vaccination. The purpose of this study was to study the changes in haptoglobin (Hp), immunoglobulin G (IgG), and adenosine deaminase (ADA) in saliva after vaccination against Lawsonia intracellularis. In addition, productivity parameters were analysed to evaluate if vaccination and changes in salivary analytes could be associated with changes in these parameters. The pigs vaccinated against Lawsonia showed an improvement in the productive parameters and a reduction in food conversion and frequency of diseases. In addition, they showed lower values of Hp (p = 0.011), IgG (p < 0.01), and ADA (p < 0.003) in saliva during the first two months of the fattening period compared to non-vaccinated pigs. It could be concluded that in our experimental conditions, the vaccination against Lawsonia intracellularis produced a significant decrease in biomarkers of the immune response in saliva compared with the non-vaccinated pigs. This would indicate a reduction in the activation of the immune system, which could be postulated to be due to the increased defence ability of the organism against pathogens. This reduced activation of the immune system can lead to better food conversion and an increase in the productive parameters of these pigs. Overall, this report opens a new window for the possible use of saliva for non-invasive evaluation of the immune system after vaccination in pigs.